Knowledge, attitudes and practices on hypertension among patients in a district hospital - Eslah H.H. Ahmed; Olga M. Maphasha; Sunday O. Okeke (South African Family Practice)
Background: Hypertension is a major global public health issue, with effective management relying heavily on patient adherence to lifestyle changes and medication. Understanding demographic influences on these behaviours is vital for targeted intervention. This study assessed knowledge, attitudes, and practices related to hypertension among patients at a district hospital in Tshwane, South Africa.